Dual living donor organ transplants. Issue 4 (5th February 2023) - Gruessner, Rainer W. G.; Gruessner, Angelika C.
Abstract: Introduction: Dual organ donation and transplantation from living donors (LDs) is a rare practice. Dual organ transplants can be done from the same LD or from different LDs and either simultaneously or sequentially. Simultaneous dual organ transplants from the same LD are of considerable concern due to the magnitude of the donor procedure. Methods and Results: According to the UNOS/OPTN and IPTR databases, the US experience of LD dual organ transplants from 1981 to 2021 comprised 101 simultaneous or sequential dual organ transplants from the same LD and 111 transplants from different LDs for a total of 212 LD dual transplants. The first simultaneous or sequential dual organ transplants from either the same LD or different LDs were pancreas‐kidney transplants (n = 92). Four additional LD organ transplant combinations have been performed in the United States: liver‐kidney (n = 93), lung‐kidney (n = 16), liver‐intestine (n = 9), and intestine‐kidney (n = 2). Only for dual pancreas‐kidney (n = 49) and liver‐intestinal transplants (n = 4), organs from the same LD have been procured simultaneously. Importantly, no donor deaths have been reported after any simultaneous or sequential procurement. LD dual organ outcomes in all recipient categories have been excellent. Conclusions: LD dual organ donation and transplantation is safe and successful. Any potential dual organ LD candidate must be subject to the highest level of evaluation scrutiny. A (dual) organ donor registry is warranted for long‐term follow‐up.